Suicidal ideation and its associated risk factors among students of a medical college in Chennai—A cross-sectional study - M Koushik; Prarthana Veeramani; L Pooja Mary Vaishali; B Charumathi; Timsi Jain (Journal of Family Medicine and Primary Care)
Introduction: Suicidal ideation is the thought or plan to suicide. It is an important public health issue. A severe cause of mortality worldwide is suicide. Previous studies have analyzed suicidal ideation in patients who have already attempted self-harm. In this study, we aim to find out the prevalence of suicidal ideation and knowledge of danger signs of suicide in a nonclinical population, especially among students of a medical college. Methodology: An institutional-based analytical cross-sectional study was conducted from February 2021 to October 2021 in a private medical college in Chennai. Data were collected from the medical students of the private medical college using Beck’s suicidal ideation scale, (DASS-21), and a semistructured questionnaire. Students aged above 18 years and willing to participate in this study were included. The sample size was calculated as 304 by taking reference value from a previous study by Ahmed et al. in Egypt. The total number of students studying in the college was 700, out of which 310 responses were obtained. Convenient sampling was done. Google forms were circulated to the students and data were collected and analyzed using SPSS version 22.0. Descriptive statistics were calculated. An association between the study variables and suicidal ideation was found by using the Chi-square test. P < 0.05 were found to be statistically significant. Results: The prevalence of suicidal ideation among the study population was found to be 9%. Factors like the presence of depression, anxiety, stress, dissatisfied lifestyle, history of smoking, drugs, and alcohol consumption were found to be contributing to suicidal ideation. About 37.7% of the study population felt that they knew about the danger signs of suicide. Conclusion: Promotion of mental health and screening for mental health disorders need to be done regularly. Identified risk factors for suicidal ideation should be addressed and mitigated.